Multi-layered graphene quantum dots derived photodegradation mechanism of methylene blue1. Issue 64 (12th July 2015) - Umrao, Sima; Sharma, Poornima; Bansal, Anushka; Sinha, Ranjna; Singh, Ranjan K.; Srivastava, Anchal
<x xml:space="preserve">Abstract</x> Efficient visible light photodegradation of methylene blue using multi-layered graphene quantum dots (MLGQDs) has been studied with clear mechanism.